2015
DOI: 10.1007/s41063-015-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

A baseline for the vertical distribution of the stable carbon isotopes of dissolved inorganic carbon (δ13CDIC) in the Arctic Ocean

Abstract: Stable carbon isotopes of dissolved inorganic carbon (d 13 C DIC ) in the ocean are generally not well understood as they are governed by a complex interplay of biological processes and air-sea exchange. In the Arctic Ocean, d 13 C DIC values are prone to change in the near future with rapidly changing climate conditions. This study provides a baseline to assess the d 13 C DIC of the Arctic Ocean with a focus on upper to intermediate waters (to *500 m). Measured d 13 C DIC values in the Arctic Ocean range from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Lynch-Stieglitz et al, 1995) at greater depth in Mosselbukta and at Bjørnøy-Banken instead may result from brine rejection during sea-ice formation and a relatively strong invasion of atmospheric CO 2 associated with sinking cold water, respectively. This is consistent with low δ 13 C as on Arctic shelf areas, mainly reflecting the invasion of isotopically light atmospheric CO 2 under non-equilibrium conditions (Bauch et al, 2015).…”
Section: Stable Carbon Isotopes Of Dissolved Inorganic Carbonsupporting
confidence: 81%
See 2 more Smart Citations
“…Lynch-Stieglitz et al, 1995) at greater depth in Mosselbukta and at Bjørnøy-Banken instead may result from brine rejection during sea-ice formation and a relatively strong invasion of atmospheric CO 2 associated with sinking cold water, respectively. This is consistent with low δ 13 C as on Arctic shelf areas, mainly reflecting the invasion of isotopically light atmospheric CO 2 under non-equilibrium conditions (Bauch et al, 2015).…”
Section: Stable Carbon Isotopes Of Dissolved Inorganic Carbonsupporting
confidence: 81%
“…. The detailed study by Bauch et al (2015) showed that air-sea exchange processes in the entire Arctic Ocean and shelf regions are far from being at equilibrium, implying that at high latitudes diffusion of CO 2 from the atmosphere into the oceanic system leads to a decrease in δ 13 C DIC and δ 13 C as (Lynch-Stieglitz et al, 1995). This is also consistently identifiable in the present relationship between pCO 2 and δ 13 C as values ( Figure 10C).…”
Section: Stable Carbon Isotopes Of Dissolved Inorganic Carbonsupporting
confidence: 67%
See 1 more Smart Citation
“…Whereas the δ 13 C CO2 value is influenced by short-term physical (sea-air exchange) and biological processes (primary production and respiration) on the order of days (biological processes) to weeks (sea-air exchange), the exchange of the DIC pool and related δ 13 C DIC signature takes decades in a coastal water body with the volume comparable to the LS [Zeebe et al, 1999]. The assumed outer end-member in our isotope mixing model of 1‰ for open waters appears also rather robust, since Shelf Break waters and ArcO are pretty stable in δ 13 C DIC [Bauch et al, 2015]. These authors also conclude that ice melting-that had already occurred in the LS during the SWERUS cruise-has a negligible effect on δ 13 C DIC signatures.…”
Section: Respiration Rate Of Oc Ter In the Laptev Seamentioning
confidence: 94%
“…To relate the temporal trend in δ 13 C‐POC water values to the predicted decline of δ 13 C‐DIC and δ 13 C‐CO 2 values, a compilation of data on δ 13 C‐DIC values was extracted from three publications (Bauch, Polyak, & Ortiz, ; Schmittner et al, ; Young et al, ) and two databases (Becker et al, ; Key et al, ). δ 13 C‐CO 2 values were determined from the δ 13 C‐DIC values and absolute temperature following the Equation (1) (Rau, Riebesell, & Wolf‐Gladrow, ).…”
Section: Methodsmentioning
confidence: 99%